Prevalence and incidence of multiple sclerosis in central Poland, 2010–2014. Issue 1 (December 2016) - Brola, Waldemar; Sobolewski, Piotr; Flaga, Stanisław; Fudala, Małgorzata; Szczuchniak, Wiktor; Stoiński, Jan; Rosołowska, Anita; Wójcik, Jacek; Kapica-Topczewska, Katarzyna; Ryglewicz, Danuta
Abstract Background Comprehensive epidemiologic data for multiple sclerosis (MS) in Poland are limited. The aim of this cross-sectional population-based study was to determine the incidence and prevalence of MS in the Swietokrzyskie Region (central Poland). Methods This study identified MS cases every year between 1 January 2010 and 31 December 2014. The study area population on the prevalence day (December 31, 2014) was 1, 263, 176 (646, 506 women and 616, 670 men). A total of 1462 patients with a clinically definite diagnosis of MS according to McDonald's criteria (2005), recorded in the Polish Multiple Sclerosis Registry, were considered for estimation of crude, age- and sex-specific prevalence, and incidence. Results The overall crude prevalence rate of confirmed MS patients was 115.7/100, 000 (95 % confidence interval (CI), 111.2–121.4). A significantly higher prevalence was recorded in females (159.6/100, 000; 95 % CI, 151.1–165.3) than in males (69.7/100, 000; 95 % CI, 62.4–77.3) (P  < 0.001). Age-adjusted rates for the Polish and European Standard Population were 109.8/100, 000 (95 % CI, 105.4–114.8) and 106.6/100, 000 (95 % CI, 101.1–111.2), respectively. The female/male ratio was 2.4. The mean annual incidence was 4.2/100, 000 (95 % CI. 3.7–4.4). Conclusion The incidence and prevalence of MS in the Swietokrzyskie region confirm that central Poland is a high risk area for MS. Compared with previous epidemiologic studies from Poland, the prevalence of MS has increased during recent years.